Virulence factors genes in enterococci isolated from beavers (Castor fiber) - Lauková, Andrea; Strompfová, Viola; Kandričáková, Anna; Ščerbová, Jana; Semedo-Lemsaddek, Teresa; Miltko, Renata; Belzecki, Grzegorz (Folia microbiologica, 2015)
Only limited information exists concerning the microbiota in beaver (Castor fiber). This study has been focused on the virulence factors genes detection in enterococci from beavers. In general, animals are not affected by enterococcal infections, but they can be a reservoir of, e.g. pathogenic strains. Moreover, detection of virulence factors genes in enterococci from beavers was never tested before. Free-living beavers (12), male and female (age 4-5 years) were caught in the north-east part of Poland. Sampling of lower gut and faeces was provided according to all ethical rules for animal handling. Samples were treated using a standard microbiological method. Pure bacterial colonies were identified by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) identification system. Virulence factors genes-gelE (gelatinase), agg (aggregation), cylA (cytolysin A), efaAfs (adhesin Enterococcus faecalis), efaAfm (adhesin Enterococcus faecium) and esp (surface protein) were tested by PCR. Moreover, gelatinase and antibiotic phenotypes were tested. Species detected were Enterococcus thailandicus, E. faecium, E. faecalis and Enterococcus durans. In literature, enterococcal species distribution was never reported yet up to now. Strains were mostly sensitive to antibiotics. Vancomycin-resistant E. faecalis EE9Tr1 possess cylA, efaAfs, esp and gelE genes. Strains were aggregation substance genes absent. Adhesin E. faecium (efaAfm) gene was detected in two of three E. faecium strains, but it was present also in E. thailandicus. Esp gene was present in EE9Tr1 and E. durans EDTr92. The most detected were gelE, efaAfm genes; in EF 4Hc1 also gelatinase phenotype was found. Strains with virulence factors genes will be tested for their sensitivity to antimicrobial enterocins.
Keywords: hlodavci; Feces; bakteriologické techniky; polymerázová řetězová reakce; Gelatinases; Male; Rectum; Virulence Factors; Genotype; Rodentia; Poland; antibakteriální látky; Bacteriological Techniques; Microbial Sensitivity Tests; mužské pohlaví; rektum; faktory virulence; Animals; Enterococcus; ženské pohlaví; grampozitivní bakteriální infekce; Anti-Bacterial Agents; Gram-Positive Bacterial Infections; zvířata; mikrobiální testy citlivosti; spektrometrie hmotnostní - ionizace laserem za účasti matrice; genotyp; Polymerase Chain Reaction; Female; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Polsko; feces; želatinasy